Analisis Puisi “Kepada Kawan” Karya Chairil Anwar Dengan Pendekatan Ekspresif - Naura Latifa; Prima Nucifera (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
The poem Kepada Kawan by Chairil Anwar is a work rich in emotion, philosophical depth, and life values, making it a timeless piece in Indonesian literature. In this poem, Chairil Anwar masterfully explores universal themes such as courage, friendship, and death, presenting them through powerful and evocative language. The poem does more than convey feelings; it invites readers into the intimate space of the poet's inner world, where existential struggles and profound reflections intertwine. This study employs an expressive approach to analyze how Chairil Anwar's emotions, thoughts, and personal experiences shape the poem, revealing the depths of his personality and worldview. The analysis delves into the connection between the poet’s emotions and his language style, uncovering how his choice of words and imagery conveys defiance against fear and regret. It also reflects the poet's existential perspective, emphasizing resilience in the face of mortality and the transient nature of life. This defiance is not merely a literary device but a reflection of Chairil's inner conflict and his pursuit of meaning and authenticity in life. The study thus offers a richer understanding of Kepada Kawan as not only a poetic masterpiece but also a window into Chairil Anwar's soul, capturing his rejection of despair and his celebration of life’s courage amidst its inevitabilities.